Earthquake relocation to understand the megathrust segments along the Sumatran subduction zone. Issue 1 (January 2021) - Jihad, Abdi; Muksin, Umar; Syamsidik,; Ramli, Marwan
Abstract: Historical seismicity shows the presence of mega-thrust segments along the Sumatran subduction zone that could generate large earthquakes. The segments include the Aceh-Andaman, Nias-Seumeuleu, Batu, Siberut, Mentawai-Pagai, Enggano, and Sunda Strait. Shallow and large earthquakes with magnitudes larger than 7.5 can occur along the segments thus trigger tsunamis. The accurate seismicity distribution along the subduction zone can be used to characterize the segments. The objective of the research is to precisely relocate the earthquakes in order to investigate the properties of the Sumatran subduction zone. Among more than 5000 preliminary located earthquakes occurring in 1980-2018 obtained from the Indonesian Agency for Geophysics (BMKG), only earthquakes with azimuthal gap angle less than 180 and recorded by at least 4 stations are used in the data analysis. We applied double difference method in order to relocate the seismic events. The result shows a zone with significantly less earthquakes along the subduction in West Aceh interpreted as a seismic gap zone. This zone is expected to accumulate energy which could be released in the form of a large earthquake. The new earthquake locations mimic shallower Sumatran subduction zone further north therefore closer to people inland. The closer earthquake the higher intensity of an earthquake felt by people which higher level of hazard. The pattern of the subduction zone derived from the relocated seismicity can be used as better source information for tsunami modeling.